Strategi Pemenuhan Kebutuhan Informasi Pengguna di Perpustakaan Prof Lafran Pane Tapanuli Selatan Berbasis Inklusi Sosial - Allya Novita Adella; Faisal Riza (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Social inclusion is a process in developing the capacity of individuals and groups to participate and play a role in society. This study aims to analyze how the strategy of fulfilling information needs in the Prof. Lafran Pane library is based on social inclusion. This study uses a descriptive research method with a qualitative approach. Data were collected through observation, interviews, and documentation. The results of the study stated that the Lafran Pane Library's strategy was quite good even though there were some obstacles in terms of the lack of interest in reading among the South Tapanuli community.